Incidence and predictors of nonresponse to Hepatitis B vaccination among dialysis patients at Chris Hani Baragwanath Hospital - Johannes, Leigh (My University, 2021)
Background: In South Africa the prevalence of Hepatitis B virus (HBV) is relatively high with studies showing HBV prevalence rates of 4.8% for males and 3.2% for females (1). Patients on dialysis have an increased risk of contracting HBV due to hematogenous and sexual spread. HBV vaccination series efficacy is known to be reduced in patients on dialysis (2). The Chris Hani Baragwanath Academic Hospital (CHBAH) renal unit uses the HBV vaccination, but no studies have been done to determine the incidence of HBV in this renal unit or the vaccine’s efficacy. Objectives: The incidence of non-response to the Hepatitis B vaccination of patients dialysing in CHBAH renal unit and predictors of non-response. Methods: Demographics and hepatitis serology of patients dialysing in September 2018 was captured and analysed. Results: The study sample consisted of 129 patients, with the mean age 43.01 and 52.7% were male. The most common cause of chronic kidney disease (CKD) was ‘unknown aetiology’ (39.5%) and 83.7% of the population was HIV negative. CHBAH renal unit has a younger population, less confirmed diabetic nephropathy patients (2.3%) and low levels of Hepatitis C infection (2.3%). Patients on haemodialysis (55%) and peritoneal dialysis (45%) were included. This study concluded that -no variable could predict seroconversion. Conclusion: CHBAH renal unit has a population which is very different to the patients in international studies, but the seroconversion rates are similar. The researcher hopes this study will create awareness to ensure that patients have appropriate protection with regard to HBV infection
A research report submitted to the Faculty of Health Sciences, University of Witwatersrand, Johannesburg, in partial fulfillment of the requirements for the degree of Master of Medicine in the branch of Internal Medicine, 2021